The Continental Clay Connection. (Regina, Sask. : Norman Mackenzie Art Gallery, University of Regina, 1980)
Fafard, Joseph ; Gilhooly, David ; Gómez, Ricardo ; James, Ann ; Keelan, Margaret ; Levine, Marilyn ; Thauberger, David ; Beauparlant, Luc ; Bova, Joseph ; Brady, Robert ; Costanzo, Tony ; Hirsch, Richard ; Kafer, Stephen ; Roloff, John
The Continental Clay Connection, Norman Mackenzie Art Gallery, University of Regina, Regina, September 12 to October 19, 1980
boek